The big sky - Guthrie, Alfred B. 1901-1991 (Bantam Books, 1982)
A legend before he turned 20, Boone Caudill was a powerful White Savage that only one woman, the beautiful daughter of a Blackfoot chief, would dare to love.
Keywords: Geschichte; Frontier and pioneer life -- West (U.S.) -- Fiction; Siksika Indians -- Fiction; Montana -- History -- Fiction